Genetic epidemiology of atopy and asthma - Wan, Yize Isalina (2011)
The evidence for genetic contributions to the development of asthma and atopy has been well established. Refining the major genetic factors underlying these contributions will lead to a greater understanding of the pathophysiology of these conditions and potentially identify novel therapeutic targets.